Examining the Organizational Commitment of the Trainers of the Ministry of Youth and Sports - Editor, Hamza Küçük; Mehmet Vakıf Durmuşoğlu (Journal of Educational Issues, 2024)
The purpose of this research is to examine the organizational commitment levels of the Ministry of Youth and Sports trainers in terms of demographic variables. The “Organizational Commitment Scale” developed by Balay (2000) to determine the organizational commitment of individuals was used as a data collection tool in the study. The scale consists of 27 items and sub-dimensions of “adaptation”, “identification” and “internalization”. The sample group of the study consists of 162 trainers. According to the results of the research, in the sub-dimension of “identification” and “internalization” of trainers, those aged 40 and over, those with 16 years of sports years and above, and team sports trainers had higher scores (p < 0.05). No difference was found according to marital status, being a national team trainer, active sports, and previous sports (p > 0.05). Depending on the age of the trainers, it can be stated that they feel like they belong to the institution they work for. With the increase in working years, it can be said that the trainers establish a bond with the institution they work instead of being directed to different fields.